2013
DOI: 10.1002/2013gl057866
|View full text |Cite
|
Sign up to set email alerts
|

Improved simulation of extreme precipitation in a high‐resolution atmosphere model

Abstract: [1] Climate models often underestimate the magnitude of extreme precipitation. We compare the performance of a high-resolution ( 0.25 ı ) time-slice atmospheric simulation of the Community Earth System Model 1.0 in representing daily extreme precipitation events against those of the same model at lower resolutions ( 1 ı and 2 ı ). We find significant increases in the simulated levels of daily extreme precipitation over Europe, the United States, and Australia. In many cases the increase in high percentiles (>… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
91
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(100 citation statements)
references
References 39 publications
8
91
1
Order By: Relevance
“…Wehner et al, 2010;Kopparla et al, 2013;Prein et al, 2013;Tripathi and Dominguez, 2013). However, several of these studies compare the results on the native grid of each model with observations at resolutions that are often higher than in any of the model configurations.…”
Section: Discussionmentioning
confidence: 99%
“…Wehner et al, 2010;Kopparla et al, 2013;Prein et al, 2013;Tripathi and Dominguez, 2013). However, several of these studies compare the results on the native grid of each model with observations at resolutions that are often higher than in any of the model configurations.…”
Section: Discussionmentioning
confidence: 99%
“…To define daily precipitation extremes, we used the percentile approach (Diffenbaugh et al 2005;Malik et al 2012;Kopparla et al 2013;Singh et al 2013). In particular, for a percentile threshold of p, we find the pth percentile of the distribution of daily rainfall over all the grids over the Asian domain.…”
Section: Methodsmentioning
confidence: 99%
“…Sensitivity experiments with the Community Earth System Model (CESM) by altering horizontal grid resolution demonstrated reduced biases at the highest resolution (0.23° × 0.31°) over Europe, the USA, and Australia (Kopparla et al 2013). Furthermore, the fraction of large-scale precipitation was seen to be larger at high-resolution (Bacmeister et al 2013;Kopparla et al 2013). Volosciuk et al (2015) found that the effects of averaging and representation of physical processes in ECHAM5 model at different horizontal resolutions vary with region and season.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations